A detailed assessment of resource of biomethane from first, second and third generation substrates. (March 2016) - Allen, Eoin; Wall, David M.; Herrmann, Christiane; Murphy, Jerry D.
Abstract: This paper details the analysis of biochemical methane potential (BMP) assessment of 83 substrates, which may be deemed as: first generation substrates (food crops); second generation (grasses and wastes); and third generation (seaweed). Significant variation in the BMP of a substrate may be found depending on for example, season and method of harvest. This could lead to significant discrepancy between energy production at the design stage and in operation of the facility. For example the BMP of dairy slurry varied from 175 L CH4 kg −1 VS in autumn (cattle fed on concentrate at end of farming year) to 239 L CH4 kg −1 VS in the summer when cattle are fed fresh grass. Grass ranged from 156 (for hay) to 433 L CH4 kg −1 VS for first cut baled silage. Saccharina latissima (brown seaweed) generated a higher BMP 36.4 m 3 CH4 t −1 than summer dairy slurry 16 m 3 CH4 t −1 . In terms of a national resource, the cheapest and most sustainable source of biomethane will be from wastes, but the resource is finite. Biomethane from wastes could satisfy 18.4% of transport energy in Ireland. Larger resources will require third generation substrates such as seaweed. Highlights: Biomethane is a source of 1st, 2nd and 3rd generation transport biofuel. Biomethane from crops can yield between 152 (grass) to 453 GJ ha −1 yr −1 (potatoes). The potential from wastes in Ireland is equivalent to 18.3% of energy in transport. Seasonal variation exists; dairy slurry yields between 175 and 239 L CH4 kg −1 VS. BMP assays do not indicate operational conditions in long term digestion.